Analisis Biaya Volume Laba Sebagai Alat Bantu Perencanaan Laba Pada Perusahaan Pia Latief Kediri - Winarko, Sigitpuji; Astuti, Puji; Wijayanti, Fitri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
Small and medium enterprises in Kediri grow rapidly, especially food business. Similarly, Pia Latief's business is also growing year by year, as evidenced by the increasing demand. So this sector needs to continue to be developed and needs to be examined how the development so as to provide input and description of his business. The analysis that needs attention is related to the sales volume associated with the cost and the profit earned. The purpose of this research is to analyze related to break even point, contribution margin, margin of safety, and profit planning. The data used are primary data and secondary data. The research approach used is quantitative approach. Data analysis using least square method to separate semi variable cost into fixed cost and variable cost. After that analyzed by using break even point, contribution margin, and margin of safety. The results of research conducted on the company Pia Latief Kediri, on two products namely wet pia and dry pia is a wet pia BEP of 6,986 units, dry pia of 12,292 units. The margin of safety contribution was 53.34% from the sales, margin of safety was 95.67% with the target of 2017 for 169,581 units for wet pia product, dry pia sales target of 298,409 units. Expected from the results of this study can provide input on the company Pia Latief in determining the policy of production and sales, so obtained a profitable advantage.